Pengembangan Media Pembelajaran Berbasis Video Tutorial Pada Matakuliah Aplikasi Komputer Untuk Pembelajaran Bagi Mahasiswa Program Studi Pendidikan Ekonomi IKIP Budi Utomo Malang - Dian, Miftah Rakhma; Fandyansari, Melisa Wahyu (Efektor, 2019)
The purpose of making this tutorial video learning media is to attract students' interest in attending the Computer Application for Learning course, making it easier for lecturers and students in the teaching and learning process, and helping students to remember the material that has been discussed by playing video. The research method used in this study adopted the Research and Development (R&D) method. The steps used in Research and Development research are: (1) identifying problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product trials , (7) product revision. Broadly speaking, the stages of making videos are grouped again into 3 main stages, namely: (1) Pre-Production Stage, this stage includes; (a) analyzing the potential and problems, (b) collecting data to solve the problem, (c) making the design of making video tutorials, (d) preparing video tutorial material, (e) preparing the description of video tutorial material, (f) preparing lines large video tutorial content, (g) validate the material, (g) make revisions. (2) Production Phase, this stage includes; (a) coordinating the results of compiling an outline of the contents of the tutorial video with the production team, (b) preparation of equipment both hardware and software, (c) Video capture. (3) Postproduction Stage, this stage includes; (a) previewing and selecting videos to be used, (b) doing the editing process (combining videos, changing or adding something to the video), (c) doing media validation, and language, (d) making revisions. The final results of this study are video media that have been validated by experts in the material, language and media that are ready to be used in learning Computer Application for Learning courses at IKIP Budi Utomo Malang.